ANALISIS DIMENSI AFEKTIF, KOGNITIF DAN PSIKOMOTOR PADA STANDAR KOMPETENSI LULUSAN SD/MI KTSP DAN KURIKULUM 2013 - Chandy Febyanto , Agus Eko Pranoto (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
At KTSP andÃƒâ€šÃ‚Â curriculum 2013 contains dimensions of cognitive, affective and psychomotor. The purpose of this research is to analyse in depth the suitability of proportion the aspects of psychomotor, cognitive and affective on the standard of competence of graduates of SD/MIÃƒâ€šÃ‚Â KTSP and curriculum 2013. In addition, to project the competence of graduates of SD/MI curriculum 2013 against global challenges. The methods used in this research is descriptive qualitative. Type a descriptive qualitative study in this research is the analysis of contents or document. The results showed that the concept of the dimensions ofÃƒâ€šÃ‚Â affective, cognitive and psychomotor in curriculum 2013 more detailedÃƒâ€šÃ‚Â and holisticÃƒâ€šÃ‚Â compared to the KTSP.